Model Project Based Learning dan Motivasi Belajar dalam Meningkatkan Hasil Belajar Sejarah Kebudayaan Islam: Kajian Teoretis - Muslimah, Ana; Subando, Joko (TSAQOFAH, 2026)
This study was motivated by the need for innovative learning models and strengthened learning motivation to improve learning outcomes in Islamic Cultural History (SKI), while teacher-centered instructional practices still limit students’ active engagement and the deep internalization of Islamic historical values. This study aimed to theoretically analyze the roles of the Project Based Learning (PjBL) model and learning motivation in improving SKI learning outcomes. The study employed a library research method by reviewing diverse literature sources, including books, scholarly journal articles, and relevant research findings on Project Based Learning, learning motivation, and learning outcomes. The data were analyzed using a descriptive-analytical approach through critical review, comparison, and synthesis of experts’ perspectives and prior research findings. The review indicated that, in theory, Project Based Learning promoted active learning, the development of critical thinking, and contextual understanding of SKI content, whereas learning motivation functioned as an internal driver that strengthened students’ engagement and persistence in the learning process, thereby exerting a positive influence on learning outcomes. Conceptually, integrating PjBL and learning motivation had a positive influence on improving students’ learning outcomes across cognitive, affective, and psychomotor domains in SKI learning. This study contributed to strengthening the concept of innovative learning in Islamic education and provided practical implications for teachers in designing SKI instruction that is more meaningful, participatory, and motivating for students.